ANALISIS PROSEDUR KELEBIHAN PEMBAYARAN PAJAK PERTAMBAHAN NILAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN BARAT - Hutagalung, Patar Alfredo Hosea; Sembiring, Yan Christin Br (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This study aims to determine the process of resolving value added tax (VAT) overpayments and find out the obstacles faced by taxable entrepreneurs in submitting value added tax overpayments at the West Medan Pratama Tax Service Office. The sample in this study is Value Added Tax Overpayment Data for 2019-2023. Data collection techniques use interview and documentation techniques. The analysis method used is descriptive. Based on the results of this study, it shows that there are still many taxpayers who apply but do not complete the documents according to the tax overpayment procedures requested by KPP Pratama Medan Barat, as well as the implementation of tax overpayment procedures by KPP Pratama Medan Barat in accordance with the procedures of the applicable laws and SOPs. The obstacles faced by the West Medan Pratama KPP are that in practice, starting from the examination until the approval of the application, the level is quite difficult and the administrative data is incomplete, as well as evidence that shows that there is an overpayment of tax, the address is incomplete and the taxpayer has difficulty contacted.